2021
DOI: 10.3389/fspas.2021.628396
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up and Validation of K2 and TESS Planetary Systems With Keck NIRC2 Adaptive Optics Imaging

Abstract: High resolution imaging (HRI) is a critical part of the transiting exoplanet follow-up and validation process. HRI allows previously unresolved stellar companions and background blends to be resolved, vetting false positive signals and improving the radii measurements of true planets. Through a multi-semester Keck NIRC2 adaptive optics imaging program, we have pursued HRI of K2 and TESS candidate planet host systems to provide the transiting exoplanet community with necessary data for system validation and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

6
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…To help rule out stellar multiplicity and close blends with nearby stars and to obtain more precise planetary radii by accounting for close-in stellar blends (Ciardi et al 2015;Schlieder et al 2021), we observed TOI-1759 with both the 'Alopeke 3 speckle imaging camera (Scott & Howell 2018) on the 8 m Gemini North telescope and the NIRC2 near-infrared adaptive-optics fed camera on the 10 m Keck-II telescope. The optical and NIR high resolution imaging complement each other with higher resolution in the optical but deeper sensitivity (especially to low-mass stars) in the infrared.…”
Section: High-resolution Imagingmentioning
confidence: 99%
“…To help rule out stellar multiplicity and close blends with nearby stars and to obtain more precise planetary radii by accounting for close-in stellar blends (Ciardi et al 2015;Schlieder et al 2021), we observed TOI-1759 with both the 'Alopeke 3 speckle imaging camera (Scott & Howell 2018) on the 8 m Gemini North telescope and the NIRC2 near-infrared adaptive-optics fed camera on the 10 m Keck-II telescope. The optical and NIR high resolution imaging complement each other with higher resolution in the optical but deeper sensitivity (especially to low-mass stars) in the infrared.…”
Section: High-resolution Imagingmentioning
confidence: 99%
“…NIRC2 is designed for the Keck AO system in Maunakea, Hawaii, USA, as a NIR imager. Observations of TOI 620 were performed with this instrument on UT 2019 May 12 so as to further constrain the parameter space of possible companions in the TOI 620 system, as part of the standard process for doing so (Ciardi et al 2015;Schlieder et al 2021). A three-point dither pattern is commonly used with NIRC2 to avoid using the noisier lower-left detector quadrant.…”
Section: Nirc2/keck IImentioning
confidence: 99%
“…We observed TOI-530 with infrared high-resolution adaptive optics (AO) imaging at Keck Observatory (Ciardi et al 2015;Schlieder et al 2021) on UT 2019 April 7. The observations were made with the NIRC2 instrument on Keck-II behind the natural guide star AO system.…”
Section: Keck/nirc2 Adaptive Optics Imagingmentioning
confidence: 99%